Impairing the useful field of view in natural scenes: Tunnel vision versus general interference - Ringer, R. V.; Throneburg, Z.; Johnson, A. P.; Kramer, A. F.; Loschky, Lester C. (My University, 2016)
A fundamental issue in visual attention is the relationship between the useful field of view (UFOV), the region of visual space where information is encoded within a single fixation, and eccentricity. A common assumption is that impairing attentional resources reduces the size of the UFOV (i. e., tunnel vision). However, most research has not accounted for eccentricity-dependent changes in spatial resolution, potentially conflating fixed visual properties with flexible changes in visual attention. Williams (1988, 1989) argued that foveal loads are necessary to reduce the size of the UFOV, producing tunnel vision. Without a foveal load, it is argued that the attentional decrement is constant across the visual field (i. e., general interference). However, other research asserts that auditory working memory (WM) loads produce tunnel vision. To date, foveal versus auditory WM loads have not been compared to determine if they differentially change the size of the UFOV. In two experiments, we tested the effects of a foveal (rotated L vs. T discrimination) task and an auditory WM (N-back) task on an extrafoveal (Gabor) discrimination task. Gabor patches were scaled for size and processing time to produce equal performance across the visual field under single-task conditions, thus removing the confound of eccentricity-dependent differences in visual sensitivity. The results showed that although both foveal and auditory loads reduced Gabor orientation sensitivity, only the foveal load interacted with retinal eccentricity to produce tunnel vision, clearly demonstrating task-specific changes to the form of the UFOV. This has theoretical implications for understanding the UFOV.
Citation: Ringer, R. V., Throneburg, Z., Johnson, A. P., Kramer, A. F., & Loschky, L. C. (2016). Impairing the useful field of view in natural scenes: Tunnel vision versus general interference. Journal of Vision, 16(2), 25. doi:10.1167/16.2.7
Keywords: Eye Tracking; Gaze-Contingent Displays; Dual Tasking; Divided Attention; Useful Field Of View; Cortical Magnification Factor